Liposome Encapsulated Astaxanthin Altered Biochemical Profile In Diethylnitrosamine (DEN) Induced Hepato Carcinoma On Swiss Albino Mice (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Cancer is a disease in which a group of abnormal cells grow uncontrollably by disregarding the normal rules of cell division. Across several cancers, Hepatocellular carcinoma (HCC) is one of the most aggressive cancers in worldwide. It is held responsible for up to 1 million deaths globally per annum. HCC is an inflammation-related cancer, as a chronic inflammatory state is necessary for cancer appearance. In this study, the drug astaxanthin and encapsulated astaxanthin was tested against HCC. Mice were divided into 7 groups; Group I: control, Group II: DEN induced, Group III: DEN + 50 mg/kg astaxanthin, Group IV: DEN + 100 mg/kg astaxanthin, Group V: DEN + 50 mg/kg encapsulated astaxanthin, Group VI: DEN + 100 mg/kg encapsulated astaxanthin, Group VII: DEN + 10 mg/kg sorafenib. Regular diet was given. Body weight, Food intake, water intake was noted. Other biochemical parameters such as ALP, AST, Albumin, proteins and TNF-α was determined. Finally, the liver was removed from each mice of different group by sacrificing them and histopathology was done. In vivo evaluation in mice models showed significant antitumor activities by both encapsulated and non-encapsulated astaxanthin at 100 mg/kg as compared with the control, DEN induced group and positive drug sorafenib. This research suggested that encapsulated astaxanthin can also be used as chemotherapeutic agent for the treatment of Hepatocellular carcinoma (HCC).